Examination of relationship between level of hearing and written language skills in 10-14-year-old hearing impaired children - Turğut, Nedim; Karlıdağ, Turgut; Başar, Figen; Yalçın, Şinasi; Kaygusuz, İrfan; Keleş, Erol; Birkent, Ömer Faruk (My University, 2015)
OBJECTIVES: This study aims to review the relationship between written language skills and factors which are thought to affect this skill such as mean hearing loss, duration of auditory deprivation, speech discrimination score, and pre-school education attendance and socioeconomic status of hearing impaired children who attend 4th-7th grades in primary school in inclusive environment.; PATIENTS AND METHODS: The study included 25 hearing impaired children (14 males, 11 females; mean age 11.4±1.4 years; range 10 to 14 years) (study group) and 20 children (9 males, 11 females; mean age 11.5±1.3 years; range 10 to 14 years) (control group) with normal hearing in the same age group and studying in the same class. Study group was separated into two subgroups as group 1a and group 1b since some of the children with hearing disability used hearing aid while some used cochlear implant. Intragroup comparisons and relational screening were performed for those who use hearing aids and cochlear implants. Intergroup comparisons were performed to evaluate the effect of the parameters on written language skills.; RESULTS: Written expression skill level of children with hearing disability was significantly lower than their normal hearing peers (p=0.001). A significant relationship was detected between written language skills and mean hearing loss (p=0.048), duration of auditory deprivation (p=0.021), speech discrimination score (p=0.014), and preschool attendance (p=0.005), when it comes to socioeconomic status we were not able to find any significant relationship (p=0.636).; CONCLUSION: It can be said that hearing loss affects written language skills negatively and hearing impaired individuals develop low-level written language skills compared to their normal hearing peers.
İşitme engelli 10-14 yaş arası çocuklarda işitme düzeyi ile yazılı dil becerileri arasındaki ilişkinin incelenmesi
Keywords: Adolescent; Child; Child Language; Cochlear Implants; Deafness; Educational Status; Female; Hearing; Hearing Aids; Hearing Loss; Humans; Male; Persons With Hearing Impairments; Schools, Nursery; Social Class; Speech Perception; Writing; adolescent; child; cochlea prosthesis; comparative study; educational status; female; hearing; hearing aid; hearing impairment; human; language development; male; nursery school; pathophysiology; patient; physiology; rehabilitation; social class; speech perception; writing